2017
DOI: 10.1002/ecy.1635
|View full text |Cite
|
Sign up to set email alerts
|

Fungi exposed to chronic nitrogen enrichment are less able to decay leaf litter

Abstract: Abstract. Saprotrophic fungi are the primary decomposers of plant litter in temperate forests, and their activity is critical for carbon (C) and nitrogen (N) cycling. Simulated atmospheric N deposition is associated with reduced fungal biomass, shifts in fungal community structure, slowed litter decay, and soil C accumulation. Although rarely studied, N deposition may also result in novel selective pressures on fungi, affecting evolutionary trajectories. To directly test if long-term N enrichment reshapes fung… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…The core of this conceptual model is well-supported by observations that added N often reduces soil microbial biomass and alters soil microbial community composition, particularly by decreasing the abundance of fungi (Frey et al, 2004;van Diepen et al, 2007van Diepen et al, , 2016Edwards et al, 2011;Morrison et al, 2016). Decreases in fungal abundance often co-occurred with reduced activities of the lignin-modifying enzymes (LMEs) phenol oxidase and peroxidase, which are mainly produced by white rot fungi to oxidize lignin and SOM (Carreiro et al, 2000;Baldrian, 2006;Sinsabaugh, 2010;Hatakka and Hammel, 2011;Frey et al, 2014).…”
Section: Introductionmentioning
confidence: 84%
“…The core of this conceptual model is well-supported by observations that added N often reduces soil microbial biomass and alters soil microbial community composition, particularly by decreasing the abundance of fungi (Frey et al, 2004;van Diepen et al, 2007van Diepen et al, , 2016Edwards et al, 2011;Morrison et al, 2016). Decreases in fungal abundance often co-occurred with reduced activities of the lignin-modifying enzymes (LMEs) phenol oxidase and peroxidase, which are mainly produced by white rot fungi to oxidize lignin and SOM (Carreiro et al, 2000;Baldrian, 2006;Sinsabaugh, 2010;Hatakka and Hammel, 2011;Frey et al, 2014).…”
Section: Introductionmentioning
confidence: 84%
“…Indeed, Cleveland and Liptzin (2007) suggested that an average soil microbial N:P ratio might be a more appropriate index of ecosystem nutrient limitation than plant N:P ratios. A recent study showed that the biogeochemical consequences of N deposition in temperate forests may be driven by the stoichiometry of the dominant trees and their associated microbes (Midgley and Phillips, 2016) while van Diepen et al (2017) found that fungi exposed to chronic nitrogen enrichment are less able to decay leaf litter. All of these studies point to the importance of multi-resource interactions in nutrient cycling in soils.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has established that the order and timing of species colonization can influence the structure and dynamics of communities through facilitation in different types of organisms ranging from bacteria to vertebrates 3 , 8 , 10 , 12 17 . In the case of aphids, for example, small species such as Rhopaloshipum padi are first to colonize grasses (e.g., wheat), while others like the larger R .…”
Section: Introductionmentioning
confidence: 99%